2019
DOI: 10.1021/acsnano.9b05349
|View full text |Cite|
|
Sign up to set email alerts
|

Metallic 1T Phase, 3d1 Electronic Configuration and Charge Density Wave Order in Molecular Beam Epitaxy Grown Monolayer Vanadium Ditelluride

Abstract: We present a combined experimental and theoretical study of monolayer vanadium ditelluride, VTe 2 , grown on highly oriented pyrolytic graphite by molecular-beam epitaxy. Using various in situ microscopic and spectroscopic techniques, including scanning tunneling microscopy/spectroscopy, synchrotron X-ray and angle-resolved photoemission, and X-ray absorption, together with theoretical analysis by density functional theory calculations, we demonstrate direct evidence of the metallic 1T phase and 3d 1 electroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Room-temperature ferromagnetism has been observed in VTe2 nanoplates 2 . However, FM order was absent in monolayer VTe2 according to 3 / 18 recent experimental studies 36,37 . The interplay between the long-range charge and spin orders in monolayer VTe2 is yet unknown.Here we investigate the different CDW phases in monolayer VTe2 by STM/STS and DFT calculations.…”
mentioning
confidence: 86%
“…Room-temperature ferromagnetism has been observed in VTe2 nanoplates 2 . However, FM order was absent in monolayer VTe2 according to 3 / 18 recent experimental studies 36,37 . The interplay between the long-range charge and spin orders in monolayer VTe2 is yet unknown.Here we investigate the different CDW phases in monolayer VTe2 by STM/STS and DFT calculations.…”
mentioning
confidence: 86%
“…97 G, XMCD hysteresis loops obtained at the Co and V L 3 edges, respectively, at 65 K, which demonstrate the ferromagnetic hysteresis loop of VSe 2 and the antiferromagnetic coupling between Co and V spins 100 to the monolayer. 105 Remarkably, traits of spin frustration have been discovered for the first time in the monolayer by systematic field-dependent magnetization and temperature-dependent susceptibility measurements ( Figure 5E), possibly due to its 2D triangular spin lattice on which three neighboring spins are unable to mutually antialigned with each other ( Figure 5F). This particular finding highlights an exciting example of the exotic quantum phases that can be hosted by 2D-vdW magnets.…”
Section: V-based Vdw Magnetsmentioning
confidence: 95%
“…It has also been suggested that the CDW transition opens an energy gap at the Fermi level that in turn suppresses the intrinsic ferromagnetic ordering 41,46–49 . Similarly, MBE‐grown VTe 2 MLs on graphite demonstrate a 4 × 4 CDW order at low temperature and XMCD measurements rule out the existence of intrinsic ferromagnetic order 50 …”
Section: Intrinsic Magnetism In 2d Tmcsmentioning
confidence: 96%